Process analyzer systems project engineering and management - Nichols, Gary D. (International Society of Automation (ISA), 2018)
Most control systems and process analyzer systems engineers have encountered communications breakdowns, task difficulties, and other obstacles on at least one project. The primary goal of this book is to help minimize or eliminate such occurrences. This book provides analyzer and control systems engineers, and other project team members with: Ways to recognize project risks and avoid them when possible; Methods for addressing unavoidable risks quickly and cost effectively; Project engineering and management methods for smoothly executing analyzer systems projects. Included are recommendations for: Defining hardware and documentation deliverables with emphasis on adhering to procurement policy; Working with team members in other disciplines and in the supply chain; Communicating among teams; Many methods presented here can be modified to meet specific project needs and applied to any discipline or type of equipment scoped in large or small, capital or maintenance, projects.